Ensino de química para alunos com deficiência visual: investigando a percepção de professores sobre o processo de conceitualização - Molena, Juliane Cristina (Universidade Federal de São Carlos, 2018)
This paper identifies the perceptions of chemistry teachers working in high school in regular classrooms and teachers in initial formation regarding the process of conceptualization in Chemistry by students with visual impairment The process of conceptualization refers to the act or effect of conceptualizing, that is, the formation of a concept based on the specificity of Chemistry as Science. Several papers report on the great challenges of teaching concepts and scientific phenomena for students with visual impairment, but they are directed to the teaching of Physics, existing a lack of proposals of teaching chemistry for this public, in an inclusive reality. The data were obtained through questionnaires with closed and open questions, wich was made available both printed and online and counted on the collaboration of 168 informants, who were separated into three groups, being: 73 professors graduated in chemistry; 70 teachers in initial training who were pursuing a degree in chemistry; and 25 with other formations. The data were analyzed by mixed methodology (qualitative and quantitative) using Content Analysis, with the aid of NVivo software, through categorization of responses. The quantitative analysis was performed with the IRAMUTEQ software, using Textual Statistical Analysis, with the method of analysis of Hierarchical Descending Classification (CHD) and analysis by similarity. The results showed that most of the participants believe that it is possible to teach concepts and chemical phenomena to students with visual impairment, but pointed out difficulties that go through this process, such as: the need of teacher training; elaboration of special resources, necessary methodologies to meet needs, working conditions of teachers, experimental adaptations, in which, often, phenomena are explained from visual observations, and application of the 3 dimensions of the specificity of the teaching of Chemistry, being the theoretical, phenomenological and representational levels.
Chemistry teaching for students with visual impairment: investigating the teachers' perception about the process of conceptualization
Keywords: Deficiência visual; Ensino de química; Conceitualização; Visual impairment; Chemistry teaching; Conceptualization; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM